Foreign Direct Investment, Aid and Terrorism: Empirical Insight Conditioned on Corruption Control - Uchenna Efobi; Simplice A. Asongu; Ibukun Beecroft (African Governance and Development Institute (AGDI), 2015)
This study checks the effect of foreign aid on terrorism and FDI, conditioned on domestic levels of corruption-control (CC). The empirical evidence is based on a sample of 78 countries for the period 1984-2008. The following findings are established: the negative effect of terrorism on FDI is apparent only in higher levels of CC; foreign aid dampens the negative effect of terrorism on FDI only in higher levels of CC; when foreign aid is subdivided into its bilateral and multilateral components, the result is mixed. While our findings are in accordance with the stance that bilateral aid is effective in reducing the adverse impact of transnational terrorism, the position that only multilateral aid is effective at mitigating the adverse impact of domestic terrorism on FDI is not confirmed because multilateral aid also curbs the adverse effect of transnational terrorism on FDI. Moreover, multilateral aid also decreases the adverse effect of unclear and total terrorisms on FDI. Policy implications are discussed.
Keywords: D74; F21; F35; 330; Foreign investment; Foreign aid; Terrorism